Design Analysis of Microcontroler Based Automatic Power Management in Photovoltaic Systems - Okandeji, A. A.; Onaifo, F.; Olaluwoye, O. O.; Ukagu, S. N.; Sosanya, B. O.; Imobhio, I. E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
This work considered the design analysis of an energy management system to control the state of battery discharge of a solar power system without any form of load discrimination, thus preventing a sudden system shut down. The state of discharge of the storage battery is monitored by the voltage level sensor. In particular, four voltage levels were used in this work namely: 11.5V (for less critical), 11.0V, 10.5V and 10.0V (for most critical load). The outputs of the sensors are then connected to a microcontroller which is programmed to isolate the loads in the order of priority. Tests result showed that at different voltage levels, specific load was disconnected from the desired voltage thus, stored energy was efficiently conserved. Accordingly, this prototype design ensures efficient energy management in photovoltaic systems.